Kün Aftare Settlements: First Reports on the Neolithization Process in the Northern Habur Valley - Ergül Kodaş; Yunus Çiftçi; Bahattin İpek; Mehmet Şan; Onur Dinç; Devrim Hasan Menteşe (Anadolu Araştırmaları)
The Neolithization process in southeastern Anatolia has been the subject of many studies over the years. However, these have primarily been concentrated around the Euphrates Basin and Tigris Valley. Meanwhile, recent studies in the Şanlıurfa region provide important information on the Neolithization process in the mountainous region between these two rivers. The 2023 Archaeological Survey of the Pleistocene and Early Holocene Period in the Artuklu, Kızıltepe, Yeşilli, and Nusaybin Districts of Mardin Province revealed many settlements dating to the Neolithic Period in the Northern Habur Valley. In this context, the settlements identified at Kün Aftare Mevkii in the Nusaybin District provide new information on the unique Neolithization process of the Northeastern Habur Valley, a key area to both southeastern Anatolia and northern Mesopotamia.